Colorimetric determination of total phenolic contents in ionic liquid extracts by paper microzones and digital camera. Issue 7 (11th March 2015) - Aid, Tiina; Kaljurand, Mihkel; Vaher, Merike
Abstract : A rapid colorimetric paper microzone assay of total polyphenols in ionic liquid extracts was developed and validated. Abstract : In recent years, there has been a growing interest in the extraction of phenolic compounds from plants by using ionic liquid (IL) solutions. In this study, a colorimetric paper microzone assay was developed to analyse total phenolic contents in five imidazolium based IL solutions with concentrations 50–100 mM. Nine herb methanol extracts and two herb IL extracts were used for validation. The method validation parameters were as follows: the linear range for gallic acid and catechin in BMImAc, EMMImSO4, BMImCl, BMImBF4 and C12 MImCl aqueous solutions was between 0.25 and 2 mM, with the exception of catechin in a C12 MImCl aqueous solution where it remained between 0.25 and 1.5 mM. LOD and LOQ values were determined for gallic acid and catechin IL solutions, whose IL structure and concentration were varied. In cases of all ionic liquids the determined LOD and LOQ values remained between 0.08–0.15 mM and 0.16–0.28 mM, respectively. The method was successfully validated against UV-Vis spectroscopy.